An analysis of the impact of the European convergence Phillips Curve: Evidence from US and Euro area in new EU member countries - Christian Friedrich; Václav Žďárek (Kiel Institute for the World Economy (IfW), 2009)
This paper examines how international investors evaluate the change in the risk-return profile often Central and Eastern European countries that recently entered the European Union (EU). By supplementing international investment position data provided by IMF's International Financial Statistics with data obtained from Lane and Milesi-Ferretti's External Wealth of Nations Mark II Database, we create a unified data set of external assets and liabilities for new EU member states (NMS) ranging from 1993 to 2007. Drawing from the so called 'push-pull' factor approach and the achievements of Modern Portfolio Theory, we then collect an extensive set of international controls and a number of local risk-return variables that served as transmission channels for the benefits of EU integration and hence, potentially attracted foreign capital. These variables finally enter a panel data model with the Feasible Generalized Least Squares, (FGLS) and linear regression method with panel-corrected standard errors (PCSE) as proposed by Beck and Katz (1995). Our results indicate that convergence towards the EU has had a significant impact on the liability side of international investment positions in NMS. Especially for debt and portfolio equity liabilities, the region's affiliation with the EU has mitigated the negative evaluation of local macroeconomic risk factors by international investors. Nevertheless, also global forces turned out to be important drivers of the recent build-up in external liabilities and show that the region's capital supply still depends on actions taken in other parts of the world.
Keywords: E31; F15; F21; 330; Capital flows; push-pull factor approach; EU enlargement; new EU member states; Kapitalmobilität; Portfolio-Investition; Auslandsverschuldung; Kapitalimport; Entwicklungskonvergenz; Phillips-Kurve; EU-Staaten (Osteuropa); EU-Staaten